Comparison of the efficacy of 4% articaine with epinephrine 1:100, 000 and 2% lidocaine with epinephrine 1:100, 000 buccal infiltration for single maxillary molar extraction: a double-blind, randomised, clinical trial. Issue 6 (July 2021) - Rayati, F.; Haeri, M.; Norouziha, A.; Jabbarian, R.
Abstract: The present study was designed to compare the efficiency of 4% articaine with epinephrine 1:100, 000 and 2% lidocaine with epinephrine 1:100, 000 in providing adequate anaesthesia for maxillary molar extraction with buccal infiltration only. In this randomised, double-blind clinical trial, 139 patients who needed maxillary molars extracting were enrolled. Individuals were randomly divided into two groups of 2% lidocaine with epinephrine 1:100, 000 treated by buccal infiltration without palatal injection and 4% articaine with epinephrine 1:100, 000 treated with the same method. Then, teeth were extracted and the pain assessed. During the extraction of teeth, 90.63% of patients in the lidocaine-treated group and 36% of patients in the articaine-treated group experienced pain (p<0.0001). In other words, the rates of successful anaesthesia with lidocaine and articaine buccal infiltration were 9.38% and 64%, respectively. Despite the better performance of articaine, it seems that some factors such as bone thickness and anatomical variations among individuals, besides the condition of the tooth, affects articaine's level of efficiency in each case.